2023
DOI: 10.1007/s10238-023-01044-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of Behçet’s disease with the risk of metabolic syndrome and its components: a systematic review and meta-analysis

Abstract: The present meta-analysis aimed to elucidate the association of Behçet’s disease (BD) with the risk of metabolic syndrome (MetS) and its components. Observational cohort studies were searched from the Embase, Web of Science, Medline, and Cochrane Library databases. The primary outcome was the association of BD with the risk of MetS and its relevant components. Effect estimates with odds ratios (ORs) were pooled using either the random-effects or fixed-effects models, according to heterogeneity. Leave-one-out s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
(111 reference statements)
1
0
0
Order By: Relevance
“…Some studies have shown that patients with BD are more likely to have metabolic syndrome (MetS), which is reported to be present in 25.52% of patients [ 110 ]. Consistent with previous reports, a study by Chen et al confirmed an important association between BD and MetS: the risk of metabolic syndrome was 126% greater in the BD group than in the healthy control group [ 111 ]. These findings revealed that BD is significantly associated with insulin resistance, diabetes mellitus, and hypertension [ 111 ].…”
Section: Obesity and Eye Diseasessupporting
confidence: 89%
“…Some studies have shown that patients with BD are more likely to have metabolic syndrome (MetS), which is reported to be present in 25.52% of patients [ 110 ]. Consistent with previous reports, a study by Chen et al confirmed an important association between BD and MetS: the risk of metabolic syndrome was 126% greater in the BD group than in the healthy control group [ 111 ]. These findings revealed that BD is significantly associated with insulin resistance, diabetes mellitus, and hypertension [ 111 ].…”
Section: Obesity and Eye Diseasessupporting
confidence: 89%